2020
DOI: 10.1186/s12886-020-01386-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of choriocapillary flow density between fellow eyes of polypoidal choroidal vasculopathy and neovascular age-related macular degeneration

Abstract: Background: To compare the choriocapillary flow density (CFD) among the fellow eyes of polypoidal choroidal vasculopathy (PCV), neovascular age-related macular degeneration (nAMD), and healthy controls using spectraldomain optical coherence angiography tomography (SD-OCTA). Methods: This is a cross-sectional study that includes the fellow eyes of 38 patients with unilateral PCV, 36 patients with unilateral nAMD, and 36 eyes from 36 healthy volunteers. The PCV group was further classified into polypoidal CNV (P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Recently, OCTA has been effectively detect typical pathological manifestations of PCV 25 . Luo et al reported similar results to ours in that the proportion of the choriocapillaris flow deficit area of PCV fellow eyes has a decreasing trend, but there was no statistical difference compared with an age-matched control group 5 . However, in the present research, the number of FVs in small sizes was lower compared to that of the controls, while the total area had no difference.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Recently, OCTA has been effectively detect typical pathological manifestations of PCV 25 . Luo et al reported similar results to ours in that the proportion of the choriocapillaris flow deficit area of PCV fellow eyes has a decreasing trend, but there was no statistical difference compared with an age-matched control group 5 . However, in the present research, the number of FVs in small sizes was lower compared to that of the controls, while the total area had no difference.…”
Section: Discussionsupporting
confidence: 83%
“…However, it has been reported 4 that there was no difference in vascular parameters of the choroidal vasculature, including the CC between the pachychoroid eyes without disease and normal eyes in a study using optical coherence tomography angiography (OCTA). Other studies 5 have found that the CC flow deficit of PCV fellow eyes decreased, but did not reach statistical difference compared to the age-matched control group. Since CC cannot be delineated directly with the current OCTA devices, careful consideration is required to reach a conclusion.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Increased CCFD has been reported not only in eyes with PCV but also in fellow unaffected eyes of PCV. 19 Unlike the retina, the choroid does not have a capillary complex. It is directly exposed to pulsatile blood flow that may result in dilatation of CNV tips leading to polyp formation.…”
Section: Pathophysiology Of Pcv As Understood By Newer Imaging Modali...mentioning
confidence: 99%
“…OCTA has unique advantages in the detection of retinal or choroidal vascular changes, the measurement of foveal avascular zone (FAZ), the quantification of vascular density (VD) in the inner retina, outer retinal circulation, or choriocapillaris. The technique has already been applied in the study of glaucoma ( 2 ) and various kinds of retinopathy, such as central serous choroidopathy ( 3 ), choroidal neovascularization ( 4 ), polypoid choroidal vasculopathy (PCV) ( 5 ), and diabetic retinopathy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%